Teknologi Komunikasi dan Kestabilan Hubungan Pada Pasangan Long Distance Marriage - Andu, Christine Purnamasari; Lista Litta; Ratih Puspita Siwi; Ayu Annisa Akbar; Teguh Hartono Patriantoro (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
The research aims to know and understand (1) supporting factors of communication stability to long distance marriage couples (2) the important points that form the basis of communication stability between long distance marriage couples. The research used qualitative descriptive methods. Theresearch was conducted in Makassar city, where research process or data and information collected toward informants were run through communication byphone, directly meet, and also use application such as whatsapp for other or additional information. This research use two kinds of data, which consist of primary and secondary data. Primary data is the result of interviewinginformants which already decided by the researcher to support this research with title “Supporting Factors of Communication Stability to Long Distance Marriage Couple”. Informants consist of ten, then analyzed by using two theories such as : Attribution Theory and Encertainty Reduction Theory. Results show (1) there are eight supporting factors to support the communication stability for long distance marriage couples (2) there are three main point that form the basis of communication stability which is the conclution of the informants responses, such as : commitment, need of each other, ask of eachother conditions.Keywords: Communication Stability, Couple, Long Distance Marriage